Impact of ultrasonography on identifying noninvasive prenatal screening false‐negative aneuploidy - Wei Li; Fanwei Zeng; Baitong Fan; Nan Yu; Jing Wu; Yun Yang; Hui Huang; Sheng‐li Li; Zhiyu Peng (Molecular Genetics & Genomic Medicine, 2020)
Abstract Background To evaluate the impact of ultrasonography on identifying noninvasive prenatal screening (NIPS) false‐negative aneuploidy. Methods Analysis of large population‐based NIPS false‐negative aneuploidy data comprising karyotypes, clinical outcomes, and ultrasound results. Results From December 2010 to July 2018, a total of 3,320,457 pregnancies were screened by NIPS performed in BGI; among them, 69 NIPS false‐negative aneuploidy cases with informed consent were confirmed, and ultrasound examination data for 48 cases were not available. Of the 21 cases with ultrasound results, 19 (90.5%) had various abnormalities on ultrasound, and two (9.5%) cases were shown to be normal on ultrasound. Additionally, six of seven live‐born fetuses (approximately 85.7%) were found to have abnormalities on ultrasound. Ventricular septal defects constituted the most frequently observed ultrasound abnormality type among the 21 NIPS false‐negative aneuploidy cases. Conclusion Application of NIPS has increased rapidly worldwide and now accounts for a large proportion of prenatal screening tests in China. This study suggests that ISUOG guideline should be followed practically, and structural abnormal ultrasound findings should not be neglected, even when NIPS produces a negative result. Combining NIPS with an ultrasound examination can further reduce the incidence of live births with aneuploidy.